2001
DOI: 10.1128/jvi.75.6.2818-2824.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sequences at the 3′ Untranslated Region of Bamboo Mosaic Potexvirus RNA Interact with the Viral RNA-Dependent RNA Polymerase

Abstract: The 3 untranslated region (UTR) of bamboo mosaic potexvirus (BaMV) genomic RNA was found to fold into a series of stem-loop structures including a pseudoknot structure. These structures were demonstrated to be important for viral RNA replication and were believed to be recognized by the replicase (C. Bamboo mosaic potexvirus (BaMV) has a flexuous rodshaped morphology (17) and comprises a single-stranded positive-sense RNA genome with a 5Ј m 7 GpppG structure and 3Ј poly(A) tail. The 6,366-nucleotide (nt) genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
2
36
0
1
Order By: Relevance
“…The importance of these structures in the BaMV replication has been demonstrated in vivo and in vitro (30,3335). The D domain and the pseudoknot were shown to strongly interact with a recombinant viral RdRp (36). In addition, it has been reported that synthesis of the minus-strand RNA initiates most frequently at the pseudoknot of the 3′-UTR, more specifically at the poly(A) residues of the pseudoknot (37).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of these structures in the BaMV replication has been demonstrated in vivo and in vitro (30,3335). The D domain and the pseudoknot were shown to strongly interact with a recombinant viral RdRp (36). In addition, it has been reported that synthesis of the minus-strand RNA initiates most frequently at the pseudoknot of the 3′-UTR, more specifically at the poly(A) residues of the pseudoknot (37).…”
Section: Introductionmentioning
confidence: 99%
“…These structures were demonstrated to be important for minus-strand RNA synthesis in vitro by use of a partially purified replicase from infected Nicotiana benthamiana (4). The interactions of the 3Ј UTR of BaMV RNA with the Escherichia coli-expressed viral RdRp core domain have been demonstrated by electrophoretic mobility shift assay and footprinting analysis (15). Mutants with substitutions, deletions, and insertions introduced into stemloop D failed to replicate efficiently in vivo, indicating that maintaining the integrity of the stem-loop structure is important for BaMV RNA replication (3).…”
mentioning
confidence: 99%
“…Although we did not detect binding of the isolated TMV-L RdRp domain to the TMV-L 3Ј-TR in our UV cross-linking assay, binding of the isolated 80-kDa RdRp domain of the bamboo mosaic virus (BaMV) 155-kDa replication protein to the BaMV 3Ј untranslated region was detected using a bandshift assay (11). The BaMV 155-kDa replication protein is analogous to the TMV 183-kDa protein and contains methyltransferase and helicase domains as well as the C-terminal RdRp domain.…”
Section: Discussionmentioning
confidence: 99%